2000
DOI: 10.1107/s0108270100007228
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal complexes with thiosemicarbazide-based ligands. XV. A square-pyramidal NiIIcomplex with an asymmetric coordination of 2,6-diacetylpyridine bis(S-methylisothiosemicarbazone)

Abstract: The title compound, [diacetylpyridine bis(S-methylisothiosemicarbazonato)]iodonickel(II), [Ni(C(13)H(18)N(7)S(2))I], is the first example of a complex involving the (2)N coordination of the isothiosemicarbazide moiety. 2,6-Diacetylpyridine bis(S-methylisothiosemicarbazone), as a potentially pentadentate ligand (N(5)), is coordinated as a tetradentate species, whereby one (deprotonated) isothiosemicarbazide moiety is coordinated in the usual way ((1)N(4)N), but the other (neutral) is bonded via the (2)N atom on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The Ni-N coordination bond lengths (Table 1) fall in the range 1.828 (3)-1.888 (3) Å and are typical for square-planar Ni II complexes with deprotonated amide ligands (Leininger et al, 2000;Leovac et al, 2000;Hlavica & Lewis, 2001;Moroz et al, 2006). The azomethine double-bond distances N2 C6 and N5 C11 [1.295 (5) and 1.301 (4) Å , respectively] are about the same.…”
Section: Commentmentioning
confidence: 93%
“…The Ni-N coordination bond lengths (Table 1) fall in the range 1.828 (3)-1.888 (3) Å and are typical for square-planar Ni II complexes with deprotonated amide ligands (Leininger et al, 2000;Leovac et al, 2000;Hlavica & Lewis, 2001;Moroz et al, 2006). The azomethine double-bond distances N2 C6 and N5 C11 [1.295 (5) and 1.301 (4) Å , respectively] are about the same.…”
Section: Commentmentioning
confidence: 93%
“…These anions are counter ions in the outer coordination sphere. In the paper [94], a Ni(II) compound with the previous ligand is described. In the presented complex the DAP-ITSC ligand coordinates asymmetrically through the pyridine N; amino N and azomethine N from one ITSC arm, and hydrazine N atom from the other ITSC arm (Figure 12c).…”
Section: Coordination Modes Of Hydrazone-type Schiff Bases Of Dap -Pe...mentioning
confidence: 99%
“…Together with the pyridine N, the ligand is coordinated by the 4 N donor set. By comparing the planarity of the same ligand in two complexes with Ni(II) [94] and Fe(III) [96] it is clear that the same DAP-ITSC ligand with different metal ions and in the presence of different anions is arranged differently in the coordination polyhedron.…”
Section: Coordination Modes Of Hydrazone-type Schiff Bases Of Dap -Pe...mentioning
confidence: 99%
“…[1][2][3]9 However, some very rare coordination modes of isothiosemicarbazones are also known, e.g., coordination through the sulfur atom of the S-alkyl moiety, 10 or lack of coordination of the isothioureido fragment. 11 Coordination of the mentioned NH 2 -group in tridentate isothiosemicarbazones results in its frequent condensation with, for example, salicyl-and pyridine-2-aldehyde 12 or 2-(diphenylphosphino)benzaldehyde, 13 thus forming complexes with tetradentate N 2 O 2 , N 3 O and N 2 OP donors, respectively. It was also found that bis(isothiosemicarbazones) of pentan-2,4-dione are able to stabilize some less usual oxidation states: Fe(IV), 14,15 Ni(III) 16 and Cu(III).…”
Section: Introductionmentioning
confidence: 99%